The Influence of Digital Readiness and Learning Styles on Self-Directed Learning and Student Learning Outcomes in Technology-Based Learning - Metta Mariam; Ida Rosnidah (MASI Mandiri Edukasi, 2026)
Technology-enhanced learning and flipped classroom approaches have become increasingly important in higher education. However, limited research has examined the integrated relationships among digital readiness, learning styles, self-directed learning, and learning outcomes within a single analytical model. This study aims to analyze the relationships among digital readiness, learning styles based on Kolb’s Experiential Learning Theory, self-directed learning, and student learning outcomes in a flipped classroom learning environment. A quantitative approach with an explanatory correlational design was employed. The sample consisted of 90 fifth-semester students in the Informatics Engineering Education program selected through purposive sampling. Data were collected using a five-point Likert-scale questionnaire and academic achievement records and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results showed that digital readiness significantly influenced self-directed learning (β = 0.45, p < 0.001), while learning styles also positively affected self-directed learning (β = 0.32, p < 0.001). Self-directed learning emerged as the strongest predictor of learning outcomes (β = 0.51, p < 0.001) and significantly mediated the relationships between digital readiness and learning outcomes (β = 0.278, p < 0.001) and between learning styles and learning outcomes (β = 0.164, p = 0.003). The model demonstrated substantial explanatory power (R² = 0.620 for self-directed learning; R² = 0.680 for learning outcomes). The findings suggest that technology integration is most effective when accompanied by strong self-directed learning skills. This study contributes to constructivist learning theory and provides practical implications for technology-enhanced and flipped classroom learning in higher education.